2009
DOI: 10.1002/macp.200900098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Characteristics on the Ultrasonic Degradation of Poly(vinylpyrrolidone) Studied by On‐line Monitoring

Abstract: Ultrasonic degradation of high molecular weight poly(vinylpyrrolidone) is monitored on‐line, by light scattering. Degradations are performed in water/methanol mixtures of various compositions at room temperature. The evolutions of the weight average molecular weight and the radius of gyration are monitored. The dependence of the radius of gyration on the molecular weight is found. The second virial coefficients (A2) of polymer samples in each solvent are found using Zimm plots. These mixtures are found to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…(5) and the value of parameters α and β in eq. (5) were obtained 1 and 0.6, respectively, the obtained order reaction is consistent with the results of Giz et al15 and Madras et al14 Nevertheless Taghizadeh et al13 reported various order of reaction for various molecular weights. The authors believed that the order of reaction can not be dependent to the molecular weight.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…(5) and the value of parameters α and β in eq. (5) were obtained 1 and 0.6, respectively, the obtained order reaction is consistent with the results of Giz et al15 and Madras et al14 Nevertheless Taghizadeh et al13 reported various order of reaction for various molecular weights. The authors believed that the order of reaction can not be dependent to the molecular weight.…”
Section: Resultssupporting
confidence: 90%
“…Giz and coworkers are suggested that the average molecular weight evolution could be approximated as14 where β is a measure of the heterogeneity of the process and left as a fit parameter. This model is fitted to experimental data and the best value of β is found to be 1/3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52] Moore et al approved this idea by an isotope labeling experiment on ultrasonic degradation of linear PEG. They demonstrated that when a single weak azo link was positioned at the center of a linear PEG chain, mechanically-induced cleavage was localized almost exclusively to the single weak site.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 In general, polymer mechanochemistry induced by an acoustic field is a nonrandom process; for example, the scission of polymer chains in solution occurs at a preferential position near the midpoint. [42][43][44] Moore et al approved this idea by an isotope labeling experiment on ultrasonic degradation of linear polyethylene glycol (PEG). They demonstrated that when a single weak azo link was positioned at the center of a linear PEG chain, mechanically induced cleavage was localized almost exclusively to the single weak site.…”
Section: Determination Of Reaction Order Of Degradation Of Cmcmentioning
confidence: 99%